Determinação do ponto de colheita da manga 'Ubá' para amadurecimento em condição ambiente - Lima, Raquel Reis (2018)
The mango tree (Mangifera indica L.) is a fruit species with a tropical climate, cultivated in many parts of Brazil. It is a fruit appreciated for its excellent flavor, aroma and nutritional composition. The 'Ubá' sleeve has been gaining space in the consumer market due to the high productivity, the fruit is small, but the pulp is juicy and tasty, with a strong yellow color and very sweet. The mango undergoes several changes during maturation, as physical changes, chemical and physiological, these changes affect the quality of the fruit. Harvesting has a direct impact on these. The period in which the mango is harvested affects its final characteristics, anticipated, the fruit can not develop completely, if late, the fruit has a compromised shelf life. The objective of this work was to determine the ideal physiological stage of maturation, for harvesting 'Ubá', for ripening in ambient condition, The physical-chemical characteristics of the mangoes were evaluated during maturation, At room temperature, verified the effect of maturation stage on post-harvest physical-chemical characteristics of mango, selecting the best stage for harvesting the 'Ubá' mango and establishing a shelf-life after harvest. The fruits for the experiment were obtained from the experimental area of the Federal University of Espírito Santo, campus Alegre, located in Rive-ES, 20 ° 45'00.4 "S 41 ° 29'14.1" W. The harvests were made in the period from November 27/2017 to January 7, 2018 in four different stages of maturation, these being 90, 105, 120 and 135 days after anthesis. The analyzes were conducted in the Laboratory of Agricultural Technology of the same University. The mangoes were transported from the field to the laboratory, where they were washed, sanitized and air-dried to initiate. Characterization analyzes of the fruit, weight, diameter and length and subsequent physical-chemical analyzes of yield, soluble solids content, pulp and peel color, texture, firmness, titratable acidity, pH, mass loss and ratios. Analyzes were performed on day of harvest (day zero) and every three days until the 12th day of storage at room temperature. For all the parameters evaluated in this study, it was observed that the stages in which the mangoes were harvested, affected the physical-chemical characteristics of the fruits. Beyond the stadiums, the period in which the sleeve was stored, contributed to these changes, being that the initial days the sleeves had undergone little change, but with the passage of time these changes became more pronounced. It was observed as mangoes harvested in stages 90 and 105 days were unable to mature completely after a harvest. The mangoes harvested at the 120 and 135 days stages were able to complete maturation. They present typical physicochemical characteristics of mature mango. It is concluded that the mangoes are suitable for harvesting from 120 days after the anthesis. Mangoes at this stage, conditioned at room temperature after harvesting, took about three days to mature and had a shelf life of approximately six days.